Returning to the Source: Revisiting Arendtian Forgiveness in the Politics of Reconciliation. Issue 161 (1st December 2019) - Grey, Sam
Abstract : The idea of forgiveness is omnipresent in the transitional justice literature, yet this body of work, taken as a whole, is marked by conceptual, terminological and argumentative imprecision. Equivocation is common, glossing moral, theological, therapeutic and legal considerations, while arguments proceed from political, apolitical and even antipolitical premises. With forgiveness as a praxis linked to reconciliation processes in at least ten countries, concerns have grown over its negative implications for the relationship between the state and victims of state-authored injustices. Many of these debates reference Hannah Arendt. Drawing from a range of Arendt's published and unpublished work, this article challenges the academic claim that forgiveness has no place in the politics of reconciliation. Through this 'returning to the source', it presents a promising mode of thinking about political forgiveness in contemporary Settler-colonial states.